Anaerobic probiotics: the key microbes for human health - El Enshasy, H. (Springer Science and Business Media Deutschland GmbH, 2016)
Human gastrointestinal microbiota (HGIM) incorporate a large number of microbes from different species. Anaerobic bacteria are the dominant organisms in this microbial consortium and play a crucial role in human health. In addition to their functional role as the main source of many essential metabolites for human health, they are considered as biotherapeutic agents in the regulation of different human metabolites. They are also important in the prevention and in the treatment of different physical and mental diseases. Bifidobacteria are the dominant anaerobic bacteria in HGIM and are widely used in the development of probiotic products for infants, children and adults. To develop bifidobacteria-based bioproducts, therefore, it is necessary to develop a large-scale biomass production platform based on a good understanding of the ideal medium and bioprocessing parameters for their growth and viability. In addition, high cell viability should be maintained during downstream processing and storage of probiotic cell powder or the final formulated product. In this work we review the latest information about the biology, therapeutic activities, cultivation and industrial production of bifidobacteria.